Defining and Measuring Green FDI An Exploratory Review of Existing Work and Evidence - Golub, Stephen S.. (OECD Working Papers on International Investment, 2011)
This paper was developed at the request of the OECD Working Party of the Investment Committee to document efforts to date to define and measure green FDI and to investigate the practicability of various possible definitions, as well as to identify investment policy restrictions to green FDI. It does so by reviewing the literature and existing work on the contributions of FDI to the environment; by providing a two-part definition of green FDI; and by discussing various assumptions necessary to estimate the magnitude of 'green' FDI.